Desvelando a presença da matemática nas provas do ENADE do curso de administração. - Corsi, Sonia Maria Martins (2019)
As a professor of Financial Mathematics in Higher Education, I was able to notice students’ difficulties regarding mathematical knowledge for manager training. Such experience motivated the present investigation about the presence of Mathematics in 2018 Business courses, official and institutional documents and ENADE tests. The present research was guided by the following question: How does Mathematics show in official and institutional documents and in ENADE questions of 2018 Business Course? The research methodology is qualitative and the methodological procedure was document analysis. The data were researched through ‘Diretrizes Curriculares Nacionais do Curso de Administração’, ‘Projeto Pedagógico’, learning plan of mathematical disciplines of the course and 2018 ENADE official tests. As a result, it was found that 2018 ENADE test highlights the Utility Dimension, but it also considers the Educational Dimension of mathematical knowledge. The questions show an interpretative, contextualized and humanistic character with few questions involving specific mathematical aspects; the statistic contents related to Quantitative Methods for Decision Making are the ones that show the most. The research also shows that competences and abilities, as described in the official and institutional documents, are presented in the tests; and mathematical abilities in general, such as analysis and interpretation of numerical, monetary and financial data, in texts, tables and graphics, were needed for solving the questions broadly regarding aspects of general and current knowledge (Global Economy, Social Responsibility and others), as well as other specific disciplines of Business Course.